Implementasi Algoritma Dijkstra Dalam Menemukan Jarak Terdekat Dari Lokasi Pengguna Ke Tanaman Yang Di Tuju Berbasis Android (Studi Kasus di Kebun Raya Purwodadi) - Muhammad Syamsuddin Yusuf; Hanifah Muslimah Az-Zahra; Diah Harnoni Apriyanti (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Botanical gardens is an institution that keeps documentation about living plants collection Purwodadi Botanical Gardens located on Surabaya Malang Km. 65 Highway, Purwodadi Village, Purwodadi District, Pasuruan Regency. Purwodadi Botanical Garden has an area of ​​85 hectares. Purwodadi Botanical Garden has plants collection of 2.002 species, 178 family, 962 genus and 11.669 specimens. With abundance of plants, an application is required that can lead the way from user's location to intended plant's location. In developing the application, it takes a method/algorithm to perform calculations to get the closest distance. The algorithm used in this study is dijkstra algorithm. The dijkstra algorithm is chosen because it has faster running time than the Bellman-Ford algorithm. To design the required applications, functional requirements identification stage is performed based on visitors' needs. As for non-functional requirements, it is about usability and compatibility. Implementation was created based on the design that has been made before. Web server was built using PHP language, while the android app uses Java language with tools Android Studio. The test was performed in black-box to test the functionality of the application and every results showed valid. While white-box testing was performed to test the dijkstra algorithm. In addition, usability testing was performed and showed satisfactory results with a percentage of 70.916% by 30 respondents.